British Medical Association and the National Health Service Bill (1946)
1946 1946 1940s 8 pages general practitioner members on regional boards and local management committees; that general practitioners will be responsible for the care of their own patients in general practitioner hospitals, which do not yet exist; that the general practitioner will consult freely with the specialist at the hospital, or work as a clinical assistant, or join his local medical society. There will be only such co-ordination as the administration makes possible. 10. In the Association's considered view, co-ordination should take place at the regional level. Regional boards should assume responsibility for the planning and administration of hospital and non-hospital medical services alike, for the building, ownership and administration of such health centres as may be developed, for the clinic and other treatment services of local authorities; in short, for all treatment as distinct from environmental services. Responsibility for a completely co-ordinated maternity service, including domiciliary midwifery, for health visiting and home nursing services should rest with the regional body. It is recognized that effective local administration may require that regional boards delegate some of their responsibility to appropriately constituted local or area bodies responsible to them, just as it is proposed to delegate responsibility for individual hospitals to local hospital management committees. The statutory responsibility for the provision of these services should be placed not upon local health authorities, but on regional bodies. 11. This proposal raises two problems. There would continue to be a divorce between environmental and treatment services. While this would be disadvantageous, it would be a great improvement on the Minister's present proposals. If the regional principle be accepted there arises the question of what would happen to the local executive council. The Association approves the functions and composition of the local executive council, but to secure co-ordinated administration is of the opinion that it should operate on a regional basis. 12. The Association's view on this part of the Bill may be summarized by stating that effective functional integration can be secured only by concentrating local responsibility, administrative, financial and other, at one level, and in the Association's view the appropriate level is the one selected for hospital services, the regional level. This regional integration is essential not only to efficient administration but in the interests of the public. CENTRAL ADVISORY MACHINERY 13. While the establishment of a Central Health Services Council drawing members from all the main health professions with a majority of medical members meets the profession's views, the Association urges the Minister to make certain changes. It wishes particularly to stress the following points: (a) The Council will give the fullest satisfaction only if its medical members are regarded as fully representative of the medical profession. It is desirable in the public interest to make impossible the appointment of medical members who are unacceptable to the Minister or to the medical profession. For this reason the Association urges that the medical members should be appointed by the Minister in agreement with the medical profession, a nominee unacceptable to the Minister or the profession being rejected. In addition, there should be a small number of ex-officio members, e.g., the Presidents of the Royal Colleges and the Chairman of Council of the British Medical Association. (b) The standing advisory committees of the Central Health Services Council, like the standing committees of other bodies, should report through the parent body, reporting to the Minister direct only in circumstances approved by that body, or in an emergency by its Chairman. The Central Health Services Council should itself appoint its committees, standing and other, and determine their terms of reference. Only in this way will the Central Health Services Council become a really effective body. HOSPITAL AND SPECIALIST SERVICES 14. The Association joins with the Government in desiring a co-ordinated hospital service regionally administered over natural hospital areas, a policy which it has consistently urged in all previous discussions. It is impossible to judge the merits of the proposed hospital administration in the absence of detailed information on the composition of regional hospital boards and local hospital management committees. If such bodies are appropriately constituted, with adequate representation of the medical profession, of experts in the voluntary hospital field and, in the case of the regional boards, of the universities, the proposals may, from the administrative point of view, conform to the profession's repeatedly expressed desires. If, on the other hand, the representatives of local health authorities are to be placed in a majority on regional hospital boards or local hospital management committees, the proposals will be in direct conflict with the views of the profession. The Government is urged to embody proposals for the composition of these bodies, and of the boards of governors of teaching hospitals, in the Bill, and not to leave them to be dealt with subsequently by regulation. 15. The method of the group management committee, common in local authority organization, does not do away with the need for an individual committee of management. Accordingly, the Association urges the establishment for each hospital of a committee of management, to be responsible for its day-to-day administration in conformity with the plan of the regional hospital board, and a medical staff 4 292/847/4/40